Fermentation innovation through complex hybridization of wild and domesticated yeasts - Bond, Ursula (My University, 2019)
The most common fermented beverage, lager beer, is produced by interspecies hybrids of the brewing yeast Saccharomyces cerevisiae and its wild relative S. eubayanus. Lager-brewing yeasts are not the only example of hybrid vigour or heterosis in yeasts, but the full breadth of interspecies hybrids associated with human fermentations has received less attention. Here we present a comprehensive genomic analysis of 122 Saccharomyces hybrids and introgressed strains. These strains arose from hybridization events between two to four species. Hybrids with S. cerevisiae contributions originated from three lineages of domesticated S. cerevisiae, including the major wine-making lineage and two distinct brewing lineages. In contrast, the undomesticated parents of these interspecies hybrids were all from wild Holarctic or European lineages. Most hybrids have inherited a mitochondrial genome from a parent other than S. cerevisiae, which recent functional studies suggest could confer adaptation to colder temperatures. A subset of hybrids associated with crisp flavour profiles, including both lineages of lager-brewing yeasts, have inherited inactivated S. cerevisiae alleles of critical phenolic off-flavour genes and/or lost functional copies from the wild parent through multiple genetic mechanisms. These complex hybrids shed light on the convergent and divergent evolutionary trajectories of interspecies hybrids and their impact on innovation in lager brewing and other diverse fermentation industries
PUBLISHED
Keywords: lager; interspecies hybrids; yeast; Genes & Society